Early detection of exacerbation of the severe acute respiratory syndrome coronavirus 2 infection using Fitbit (DEXTERITY pilot study). (14th October 2021) - Yamagami, K; Nomura, A; Kometani, M; Shimojima, M; Sakata, K; Usui, S; Furukawa, K; Takamura, M; Okajima, M; Watanabe, K; Yoneda, T
Abstract:  : Some patients with coronavirus disease 2019 (COVID-19) experienced sudden death because of sudden symptom deterioration. Thus, an alarm system that could detect early signs of COVID-19 exacerbation beforehand, to prevent serious illness or death of patients while receiving outpatient treatment at home or in hotels is necessary. Here, we tested whether estimated oxygen variations (EOV), a relative physiological scale that represents users' blood oxygen saturation level during sleep measured by Fitbit, predicted COVID-19 symptom exacerbation. Study period was from August to November 2020. We enrolled 23 COVID-19 patients diagnosed by SARS-CoV-2 polymerase chain reaction-positive (mean age ± standard deviation, 50.9±20 years; 70% female), let each patient wore the Fitbit for 30 days; COVID-19 symptoms were exacerbated in 6 (26%). High EOV signal (a patient's oxygen level exhibits significant dip and recovery within the index period) had 80% sensitivity before symptom exacerbations, whereas resting heart rate signal only had 50% sensitivity. Coincidental obstructive sleep apnea syndrome confirmed by polysomnography was detected in a patient by consistently high EOV signals. This pilot study successfully detected early COVID-19 symptoms exacerbation by measuring EOV and may help to identify early signs of COVID-19 exacerbation. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The investigational device used in this study, Fitbit Charge 3, was provided by Fitbit Japan.